Writing to the future: poetika at politika ng malikhaing pagsulat - Tolentino, Roland B. (Intramuros, Manila: National Commission for Culture and the Arts: Likhaan UP Institute of Creative Writing, 2008)
A collection of essays of personal poetics as shared by the fellows of the UP National Writers Workshop.
Includes bibliographical references.
English and Tagalog.
Keywords: Political poetry, Filipino; Filipino poetry -- Political aspects; Short stories, Filipino -- Political aspects